PENGARUH METODE LATIHAN PLIOMETRIK DAN MAXEX DENGAN KEKUATAN TERHADAP KECEPATAN TENDANGAN SABIT PENCAK SILAT DI STKIP SETIA BUDHI RANGKASBITUNG - Ridwan Sudirman (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2015)
The Influence Of Plyometrics Training Method And Maxex With Strength Toward Speed Of Tendangan Sabit Pencaksilat In STKIP Setia Budhi Rangkas Bitung.The purpose of this study was determine the influence of plyometrics training method and maxex with strength of speed tendangan sabit Pencak Silat in STKIP Setia Budhi Rangkasbitung Lebak-Banten 2013. This research used a factorial design experiment with 2x2. Sampling using cluster random sampling, the number of sample are60 people and divided into four groups, each group consist of 15 people. Analysis data using Analysis of variance (ANAVA) and further test wit test Tukey.This  research  concluded  that:  (1)  Overall  there  are  significant  differences  betweenPlyometrics training  method  treatment and  Maxex training  method  toward  speed  of Tendangan Sabit Pencak Silat, (2) There is interaction between Plyometrics training method and Maxex with strength toward Tendangan Sabit Pencak Silat, (3) For the group of students who have high strength, the speed of Tendangan Sabit higher when trained with Maxex training method, (4) For the group of students who have low strength, the speed of Tendangan Sabit higher when trained with Plyometrics training method. Keywords: Plyometrics, Strength toward speed, tendangan sabit.